How does big data affect organizational financial performance in turbulent markets? The role of customer-linking and selling capabilities - Itani, Omar S. (2024)
The information age provides vast opportunities for organizations to improve their efficiencies by relying on big data-AI empowered analytics (BDA). The purpose of this study is to address the critical question of how BDA-fit affects organizational financial performance, taking into consideration differences between markets and customer change caused by technology turbulence. Using data collected at the firm level and building on Task-Technology Fit Theory and Dynamic Capabilities Theory, empirical results indicate that BDA-fit is important to drive organizational financial performance through the development of customer-linking and selling capabilities. These results vary across markets, with BDA-fit having stronger effects on selling capabilities and organizational financial performance in highly turbulent markets. BDA allows organizations to upturn challenges and hindrances caused by market turbulence into opportunities to increase sales revenues. Based on the findings, theoretical contributions and managerial implications are provided.